PENGARUH PELATIHAN DAN INSENTIF TERHADAP KINERJA KARYAWAN BAGIAN MARKETING PT. NASMOCO GOMBEL SEMARANG - Amanda Bounita Rizki; Saryadi Saryadi; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2013)
Human resources becomesone of the factors that encourages the creationo the company’s competitive advantages over competitors. The purpose of this research is to find out the influence of training and incentive toward employee’s performance of marketing divison PT. Nasmoco Gombel Semarang. Type of this research is explanatory research. Number of samples taken are 30 respondents with census method or examine the whole population. Collecting data using questionnaires. Hypothesis testing using statistical analysis includes correlation coefficient, coefficient of determination, t-test and F test. Result of this study showed that the training had an influence on the employee’s  performance by 58,3% and incentive had an influence on the employee’s performance by 58,4%. Then training and incentive together have a significant influence on the employee’s performance by 64,4%.